Hubungan Kelahiran Premature Dengan Kejadian Asfiksia di Ruang Cempaka I NICU dan Neonatus RSUP Prof. Dr.I.G.N.G Ngoerah: The Relationship between Premature Birth and Asphyxia in the Cempaka I NICU Room and Neonates at RSUP Prof. Dr. I.G.N.G Ngoerah - Resiyanthi, Ni Komang Ayu; Lestari, Ni Kadek Yuni; Widiyani, Kadek (Jurnal Abdi Keperawatan dan Kedokteran, 2023)
Asphyxia is still a cause of morbidity and mortality in neonates in both developing and developed countries. Most of the asphyxia babies did not receive adequate treatment so that many of them died. The aim of this study was to determine the relationship between premature birth and the incidence of asphyxia. This research uses a correlational descriptive research type with a retrospective approach.. The sample in this study were 40 medical records of premature babies with asphyxia using the total sampling. Data analyzis using the Spearman Rank test. The results showed that the incidence of premature birth, mostly born at very preterm gestation (UK 28-31 weeks) totaling 17 respondents (42.5%) and the incidence of asphyxia was obtained mostly with a diagnosis of severe asphyxia amounting to 21 respondents (52, 5)%. The results of the analysis using the spermaman rank obtained a p-value of 0.006 and a correlation coefficient of 0.425. Comparing the p-value of 0.006 <smaller than 0.05, statistically there is a relationship between premature birth and the incidence of asphyxia. Seeing the level of strength of the relationship between preterm birth and the incidence of asphyxia, it can be said that it has an adequate relationship with the direction of the relationship being positive by looking at the r value of 0.425. Based on the research results, pregnant women are expected to regularly make ANC visits, so that risks can be detected earlier and complications will receive treatment as soon as possible.